Capacitação online e construção e validação de vídeos educativos: cuidados e manutenção do cateter venoso central de curta permanência em pacientes adultos críticos para a equipe de enfermagem - Gorla, Bruna Caroline (Universidade Federal de São Carlos, 2022)
Objectives: to assess the nursing team's knowledge before and after an online educational intervention and to build and validate scripts and storyboards for the production of educational videos, in digital format, on the care and maintenance of the short-stay central venous catheter in critically ill adults. Method: The study was divided into two phases. The first was a quasi-experimental study of the pre and post type developed with the nursing team of a University Hospital where a knowledge test form was applied before and after an educational intervention in the form of online training. In the second phase, a methodological study of quantitative approach was developed for the construction of educational videos, developed in three stages: development of scripts and storyboards, validation and production of educational videos. The development of the scripts and storyboards was based on bundles founded on good practices based on scientific evidence. For the validation of the scripts and storyboards, instruments for the evaluation of agreement were used, carried out by a committee of judges selected according to Fehring's criteria. Agreement value equal to or greater than 0.80 was considered, calculated using the Content Validity Index (CVI). Results: Regarding the first phase of the research, 21 nurses and 20 nursing technicians participated, totaling 41 participants. A descriptive analysis was conducted, considering the total score, that is, the hits achieved in the questionnaire, with all participants and for the professional categories participating in the research (nurses and nursing technicians) in the pre- and post-intervention moment, where an increase in the mean of hits was evidenced, as well as a reduction in variance in the post-intervention moment. A total of 30 participants increased their scores, that is, 73.2% of the sample showed a better performance on the questionnaire. In the second phase, the validation process occurred in only one step of the Delphi Technique, and the judges committee was composed of 11 (100%) participants, 9 subject matter expert judges, and 2 technical experts in video. The level of agreement between the video and theme expert judges obtained a CVI of 1.0. The descriptive suggestions made by the judges were analyzed, and, when appropriate, were acted upon. Thus, three scripts and storyboards resulted from this process. Subsequently, the videos were recorded in a simulated environment, edited, and made available for professional education in a Federal Public University Hospital. Conclusion: The educational intervention performed with the nursing team demonstrated an improvement in the questionnaire score at the post-intervention moment. The educational videos were made available after the judges participated in all stages, ensuring the theoretical and practical relevance of the result. It is believed that the results of this study allow the development of other strategies for the development and evaluation of the knowledge of the nursing team on the subject addressed, and it is expected that the health institution will use the material constructed and validated for the educational practice of the nursing team.
Online training and construction and validation of educational videos: Care and maintenance of the short -term central venous catheter in critical adult patients for the nursing staff
Keywords: Cateterismo venoso central; Educação em enfermagem; Cuidados de enfermagem; Filme e vídeo educativo; Tecnologia educacional; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM MEDICO-CIRURGICA